Psychological Adaptation, Marital Satisfaction, and Academic Self-Efficacy of International Students - Bulgan, Gökçe; Çiftçi, Ayşe (Journal of International Students, 2018)
The authors investigated marital satisfaction and academic self-efficacy in relation to psychological adaptation (i.e., psychological well-being, life satisfaction) in a sample of 198 married international students. Results of multiple regression analyses indicated that marital satisfaction and academic self-efficacy accounted for 45.9% of variance in psychological well-being and 25.8% of variance in life satisfaction scores. Based on the results, the differences between cognitive and emotion-oriented processes during psychological adaptation were explained. The authors discuss implications for programs with international students and mental health professionals working in university campuses.